Intercomparison of Gamma Cell 220 Irradiator Facilities and Dr. Mirzan T Razzak Gamma Irradiators Using Harwell Dosimeters - Bimo Saputro (BATAN, 2021)
The gamma irradiator is a multi-purpose facility that possibly used to preserve food, sterilize medical equipment, and conduct genetic engineering and polymerization processes, during which the absorbed dose of the product is critical. The standardization of product quality assurance was regulated by the IAEA Technical Document Number 409 considering Dosimetry for Food Irradiation and ISO 14470 and 11137-3 on Food Irradiation, as well as the Guidance on Dosimetric Aspects of Development, Validation, and Routine Control, respectively. The absorbed dose was influenced by the movement of the product to the source, its position, the amount of radioactive activity in the facility, and the dose rate in the irradiation room. The dosimeter performance test and quality assurance of the system were conducted using the Facility Intercomparison Technique which tested the dosimeter (measuring instrument) at 2 different facilities to determine the performance of the measuring instrument.. In this study, 2 irradiation facilities were tested using a Harwell routine dosimeter in the dose range of 1 kGy to 30 kGy and 20 dose points. The results showed that the highest deviation reached 19% and 21% at the Gamma Cell 220 and the Dr. Mirzan T Razzak Gamma irradiator facilities. This elevated the performance of the dosimeters to determine the precision accuracy of the dose-measuring instrument.